Does abnormal lending behavior increase bank riskiness? Evidence from Turkey - Farrukh Shahzad; Zeeshan Fareed; Bushra Zulfiqar; Umme Habiba; Muhammad Ikram (Financial Innovation, 2019)
This study empirically analyzes whether the rapid growth of loans and risk-taking behavior during the expansion of loans affected non-performing loans (NPLs) and the solvency of financial institutions in the Turkish banking system.
Keywords: 650; Turkish banks; Non-performing loans; Loan growth; Solvency; GMM